The Impact of the May 1921 Superstorm on American Telecommunication Systems - Jeffrey J. Love; Greg M. Lucas; Anna Kelbert; Neesha R. Schnepf; Paul A. Bedrosian; Sara K. McBride; Edward J. Oughton (Space Weather, 2025)
Abstract A compilation is presented of impacts (interference and damage) realized on long‐line telegraph and telephone systems across North America during the 13–16 May 1921 magnetic storm. Impacts occurred primarily during local nighttime, after the third of four sudden commencements, and during the storm's most‐prominent main phase. Impacts are attributed to rapid and high‐amplitude geomagnetic field variation generated by substorms. This induced potential differences and between the grounding points of communication networks that were sufficient to cause system interference and damage. In the United States, impacts were concentrated in the Midwest and in the East, regions characterized by high electromagnetic surface impedance. Given technological changes, modern telecommunication systems are less exposed to storms like that of May 1921, while power‐grid systems are now more exposed to them.